Proposta de método para avaliar o controle da produção e dos materiais em empresas do tipo engenharia contra pedido (engineering-to-order) - Valer, Cristiano (Universidade do Vale do Rio dos Sinos, 2011)
This work has as a goal the proposition of an method of evaluation an analysis of the production control and of the materials focused in the MES functionalities. The method is dedicated to companies that work with the logic of the engineering-to-order. At first, a bibliographic research was done looking for subjects related to: Production Systems; Production Systems Classifications; Toyota Production System; Planning Programming and Control of Production and Materials; Workstation Management; Capacity X Demand and Manufacturing Execution System. Once the theoretical framework proposed, the research was done by adopting an Holistic single case study. Finished the selection of research method, there were outlined the steps of the work method. In the sequence, it was proposed the method of assessment and analysis of the function of control of production and materials. In the development of this work, it was detailed the PPCPM of the company and of the production processes, planning, programming and control. After the overview of the processes of the company, analyzing the functionalities of the manufacturing execution system for companies of the engineering upon request type, it were mapped the functionalities that exist and that are necessary for the company improvement of the accuracy of the information for the PPCPM. After the case study, it were collected the main points for improvement focused on the control function of the PPCPM, this improvement points were analyzed by focusing on control systems for factory-floor type MES (Manufactory Execution System). As the conclusion, it was noted that the built method was robust and synchronized with the reality faced within the company used to perform the case study.
Keywords: Planejamento, programação e controle da Produção; Materiais MES (Manufactury Execution System); Engenharia contra pedido (engineering-to-order); Controle de produção; Planning, programming and control of production and materials; Engineering-to-order; Production control; ACCNPQ::Engenharias::Engenharia de Produção